Experimental Study on Flexural Properties of Self-Compacting Concrete Composite Slab with Profiled Steel Deck and the Presence of Reinforcement Bar - Khairudin, Nur Khalisah; Goh, Wan Inn (Recent Trends in Civil Engineering and Built Environment, 2024)
This paper focus on experimental study on flexural properties of self-compacting concrete composite slab with profiled steel deck and the presence of reinforcement bar. The slab samples were designed and tested under 4-point load test. The workability of Green Self-Compacting Concrete (GSCC) under filling ability and passing ability have been determined. In addition, performance of GSCC composite slabs with the presence of longitudinal reinforcement bar based on ultimate load, load-deflection response, strain development in concrete and steel and failure modes was studied in this research. Next, the longitudinal shear bond behaviour and GSCC composite slab strength with the presence of longitudinal reinforcement bar was experimentally investigated. The 4-point load test results of the composites slabs shows that GSCC composite slab with reinforcement bar was higher in ultimate load by 4.65%. In addition, the mid-span deflection can be reduced by 30.27% with inserting additional reinforcement bar into the composite slab. In the other hand, reinforcement bar added to the composite slab show higher load capacity as well as significant ductility compared to composite slab without reinforcement bar.